REPRODUCIBILITY OF MODIFIED WALDENSTRÖM CLASSIFICATION IN PERTHES DISEASE - FELIPPI GUIZARDI CORDEIRO; PATRICIA MORENO GRANGEIRO; BRUNO SÉRGIO FERREIRA MASSA; NEI BOTTER MONTENEGRO; ROBERTO GUARNIERO (Acta Ortopédica Brasileira, 2021)
ABSTRACT Objective: The purpose of our study is to evaluate intraobserver and interobserver reliability of modified Waldenström classification system for Legg-Calvé-Perthes disease and assess the influence of the professional’s area of expertise in the assessment. Methods: Twelve evaluators assessed 40 pairs of pelvic radiographs of patients with Legg-Calvé-Perthes disease. After two weeks, a new evaluation was performed by the same evaluators. Kappa and Kendall’s W indexes were used to evaluate both intraobserver and interobserver reliability and determine the influence of the evaluators’ experience and area of expertise. Results: The average intraobserver kappa value was 0.394, with a reasonable agreement level. The interobserver Kappa value was 0.243 in the first evaluation (95% CI, 0.227-0.259 and p < 0.0001) and 0.245 in the second evaluation (95% CI, 0.229-0.260 and p < 0.0001). The Kendall’s W values obtained for pediatric orthopedists, radiologists and resident physicians were 0.686, 0.630 and 0.529 (p < 0.0001), respectively. Conclusion: The modified Waldenström classification presented both moderate and reasonable levels of intraobserver agreement, and reasonable level of interobserver agreement. The evaluators’ degree of experience and area of expertise influenced the concordance level found. Level of Evidence II, Diagnostic Studies - Investigating a Diagnostic Test.